Psychological impact of the COVID-19 on hospitalized patients: A qualitative study - Fatemeh Ghapanvari; Peyman Namdar; Mahnaz Moradi; Leili Yekefallah (Wolters Kluwer Medknow Publications, 2022)
Background: As the 2019 coronavirus spreads rapidly around the world, it has caused widespread fear and anxiety in various populations. This study aimed to explore the psychological effects of COVID-19 on patients with this disease. Materials and Methods: A qualitative study was conducted with a phenomenological approach. A purposive sample of 11 patients with COVID-19 was recruited. Data were collected from the beginning of March to the beginning of June 2020 using semi-structured interviews and they were analyzed according to Van Manen's method. Interviews were audiotaped, transcribed verbatim, and analyzed using thematic analysis. Results: Initially, 315 codes were extracted. During data analysis and comparisons, the codes were reduced to 108. Ultimately, 10 categories, 38 subcategories, and 3 themes emerged. The theme of "behavioral responses" including 5 categories (Remorse, Fear and despair, Death anxiety, Growth, Support), "disease-caused helplessness" including two categories (Failure, Denial), and "decline of social networks" including three categories (Rejection, Stigma, Feeling guilty). Conclusions: After understanding the findings of this research, nurses working in the wards of patients with COVID-19 can better consider the importance of assessing and analyzing the psychological challenges and experiences of these patients during the course of illness and quarantine. Findings also enhance the identification and organization of training needs during such a pandemic and the design of nursing programs to meet them.